Redo coloanal anastomosis for anastomotic leakage after low anterior resection for rectal cancer: an analysis of 59 cases. (3rd January 2018) - Westerduin, E.; Borstlap, W. A. A.; Musters, G. D.; Westerterp, M.; van Geloven, A. A. W.; Tanis, P. J.; Wolthuis, A. M.; Bemelman, W. A.; D'Hoore, A.
Abstract: Aim: The construction of a new coloanal anastomosis (CAA) following anastomotic leakage after low anterior resection (LAR) is challenging. The available literature on this topic is scarce. The aim of this two‐centre study was to determine the clinical success and morbidity after redo CAA. Method: This retrospective cohort study included all patients with anastomotic leakage after LAR for rectal cancer who underwent a redo CAA between 2010 and 2014 in two tertiary referral centres. Short‐ and long‐term morbidity were analysed, including both anastomotic leakage and permanent stoma rates on completion of follow‐up. Results: A total of 59 patients were included, of whom 45 (76%) were men, with a mean age of 59 years (SD ± 9.4). The median interval between index and redo surgery was 14 months [interquartile range (IQR) 8–27]. The median duration of follow‐up was 27 months (IQR 17–36). The most frequent complication was anastomotic leakage of the redo CAA occurring in 24 patients (41%), resulting in a median of three reinterventions (IQR 2–4) per patient. At the end of follow‐up, bowel continuity was restored in 39/59 (66%) patients. Fourteen (24%) patients received a definitive colostomy and six (10%) still had a diverting ileostomy. In a multivariable model, leakage of the redo CAA was the only risk factor for permanent stoma (OR 0.022; 95% CI 0.004–0.122). Conclusion: Redo CAA is a viable option in selected patients with persisting leakage after LAR for rectal cancer who want their bowel continuity restored. However, patients should be fully informed about the relatively high morbidity and reintervention rates.